Seasonal change in body composition and physique of team sport athletes - Walker, E. J.; Aughey, R. J.; McLaughlin, P.; McAinch, A. J. (The Journal of Strength and Conditioning Research, 2022)
Body composition of team sport athletes was measured at 3 points across the preseason and competitive season. This repeated-measures study was conducted in 46 professional Australian football (AF) (age 23.8 ± 3.8 years), 26 soccer (age 22.7 ± 4.7 years), and 33 rugby union players (age 28.1 ± 4.2 years). A mixed-design analysis of variance was used to determine change across the season, and Pearson's correlation was used to determine the relationship between different measures. Anthropometry, dual-energy x-ray absorptiometry (DXA), and 3-dimensional (3D) scan technology were used in AF and soccer, whereas only DXA was used in rugby. Body mass remained unchanged for both AF and soccer with gains in lean mass (p < 0.01), from preseason to early in the competitive season. Skinfold measures declined in AF (p < 0.001) and soccer (p < 0.05) across the season, whereas DXA-measured fat mass only declined in soccer (p < 0.01). Rugby backs (p < 0.01) and forwards (p < 0.001) reduced body fat and gained lean mass from preseason to in-season with forwards having greater relative and absolute changes as measured by DXA. 3D technology did not show change across the season. Dual-energy x-ray absorptiometry body fat percent and the sum of skinfold correlation were large (r = 0.74 [p < 0.001, CI 0.67-0.81]). The greatest change in body composition occurs from the beginning of preseason to the start of competition, with changes returning to baseline levels toward the end of season. Dual-energy x-ray absorptiometry and skinfold measures were moderately correlated, providing a good alternative to track change in subcutaneous fat in AF and soccer athletes.